Stain control with two modified stannous fluoride/sodium tripolyphosphate toothpastes: A randomised controlled proof of concept study. Issue 2 (November 2019) - Mason, Stephen; Young, Sarah; Qaqish, Jimmy; Frappin, Guillaume; Goyal, Chhaju
Abstract: Objective: To compare build-up of extrinsic tooth stain following use of two novel anhydrous stannous fluoride/sodium tripolyphosphate (SnF2 /STP) toothpastes with adjusted (lower) relative dentin abrasivities (RDAs) versus a marketed control and a reference toothpaste. Methods: Following prophylaxis, 220 adults with extrinsic dental stain on anterior teeth facial surfaces were randomised to 4 weeks' twice-daily brushing with either novel 0.454% w/w SnF2 (1100 ppm fluoride)/5% w/w STP toothpastes with differing levels of abrasive silica: 'Test RDA∼58'; 'Test RDA∼77', or a reference: 'Ref RDA∼80′ (1000 ppm fluoride from sodium monofluorophosphate) or marketed control toothpaste: 'Ref RDA∼120′ [0.454% w/w SnF2 (1100 ppm fluoride)/5% w/w STP]. Primary endpoint was total Macpherson modification of the Lobene Stain Index (MLSI) area × intensity (A × I) score at Week 4 for Test toothpastes versus Ref RDA∼80. Secondary endpoints were total MLSI (A × I) for all toothpastes versus Ref RDA∼120. Results: After 4 weeks, mean total MLSI scores for Test RDA∼58, Test RDA∼77 and Ref RDA∼80 were all lower than Ref RDA∼120. Ranking order of performance for controlling stain build-up was: Test RDA∼77 > Test RDA∼58 > Ref RDA∼80 > Ref RDA∼120. There was no statistical difference between Test RDA∼58 and Ref RDA∼80; Test RDA∼77 was statistically lower than RDA∼80. All toothpastes were generally well-tolerated. Conclusion: This study showed low levels of stain build-up after 4 weeks' twice-daily use of novel, low abrasivity, anhydrous SnF2 toothpaste formulations (RDA∼58, RDA∼77), similar to marketed toothpastes (RDA∼80; RDA∼120). Lowering the RDA of appropriately formulated SnF2 toothpastes therefore may not negatively impact stain build-up potential (Clinicaltrials.gov NCT03160703). Clinical significance statement: This study indicates lowering RDA of an anhydrous SnF2 toothpaste does not appear to negatively impact its overall dental stain control potential. Development of appropriately formulated SnF2 toothpastes with lower abrasivity may have additional benefits for individuals with dentin hypersensitivity by managing potential dentin wear.